Supporting team coordination on the ground: requirements from a mixed reality game - Fischer, Joel E.; Jiang, Wenchao; Kerne, Andruid; Greenhalgh, Chris; Ramchurn, Sarvapali D.; Reece, Steve; Pantidi, Nadia; Rodden, Tom (2014)
We generate requirements for time-critical distributed team support relevant for domains such as disaster response. We present the Radiation Response Game to investigate socio-technical issues regarding team coordination. Field responders in this mixed-reality game use smartphones to coordinate, via text messaging, GPS, and maps, with headquarters and each other. We conduct interaction analysis to examine field observations and log data, revealing how teams achieve local and remote coordination and maintain situational awareness. We uncover requirements that highlight the role of local coordination, decision-making re- sources, geospatial referencing and message handling.